Retinal vein occlusion: A form of venous thrombosis or a complication of atherosclerosis? - Janssen, Mirian C. H.; den Heijer, Martin; Cruysberg, Johannes R. M.; Wollersheim, Hub; Bredie, Sebastian J. H. (Thrombosis and Haemostasis, 2005)
Previous studies have shown an increased risk of retinal vein occlusion (RVO) in patients with hypertension, hypercholesterolemia and diabetes mellitus. Literature on the association between thrombophilic factors and RVO consists of small studies and case reports. The objective was to determine the relationship between thrombophilic risk factors and RVO. Thrombophilic risk factors analyzed were hyperhomocysteinemia, MTHFR gene mutation, factor V Leiden mutation, protein C and S deficiency, antithrombin deficiency, prothrombin gene mutation, anticardiolipin antibodies and lupus anticoagulant. For all currently known thrombophilic risk factors odds ratios for RVO were calculated as estimates of relative risk. The odds ratios were 8.9 (95% CI 5.7 –13.7) for hyperhomocysteinemia, 3.9 (95% CI 2.3 – 6.7) for anticardiolipin antibodies, 1.2 (95% CI 0.9 –1.6) for MTHFR, 1.5 (95% CI 1.0 – 2.2) for factor V Leiden mutation and 1.6 (95% CI 0.8 – 3.2) for prothrombin gene mutation. In conclusion, regarding thrombophilic risk factors and RVO there is only evidence for an association with hyperhomocysteinemia and anticardiolipin antibodies, factors that are known as risk factors for venous thrombosis as well as for arterial vascular disease. The minor effect of factor V Leiden mutation and the protrombin gene mutation (risk factors for venous thrombosis only) suggests that atherosclerosis might be an important factor in the development of CRVO.
Keywords: Retinal vein thrombosis; retinal vein occlusion; risk factors; hyperhomocysteinemia; anticardiolipin antibodies